Avaliação da aquisição de habilidades em anestesia local odontológica através de três estratégias de ensino - Nascimento, André Luiz de Oliveira (2017)
The painless odontological treatment is one of the main goals of the dental surgeonand the local anesthesia is the most common used to reach it. Abilities and skills in odontological anesthesia can be acquired through different teaching methods. Thus, the objective of this work was to evaluate if there is a more effective teaching method for the teaching of the blockade of the inferior alveolar nerve technique and for the control of anxiety related to performing this technique. Odontology under graduate students at pre-clinical level were divided into three groups according to the type of teaching methodology used. At the Problem Based Learning (PBL) group, activities were performed in the tutorial model using a problem designed to achieve learning goals related to the technique. In the EXP group, the transmission of knowledge happened through classic expositive class. Whereas in the LAB group, activities in anatomical models were used as a way to present the anesthetic technique. Then, students were assessed in practice, through an objective structured clinical examination (OSCE) centered in the administration of the anesthetic technique and measuring the levels of anxiety before and after the execution of the procedure. There was also a theoretical evaluation related to execution aspects of the technique studied. Forty-one students concluded the practical test and the results did not show significant difference between the means of the groups ABP (12.62), EXP (13) and LAB (12.13). In the assessment of anxiety arising from the implementation of the procedure, the students of the LAB group seemed to be less anxious. On the other hand, the EXP group showed a positive correlation between anxiety and performance. In the theoretical evaluation, the average of the scores was equal for all groups (13.20). Considering the limitations of the study, it was found that the methodologies studied proved equally efficient when it comes to teaching the blockade of the inferior alveolar nerve technique. Pre-clinical practices seem to reduce the anxiety related to the execution of the technique, although this reduction has not produced a better clinical performance.